Development of the PCR Assay with Universal Primers for the Detection of Different tcpA Gene Variants - A. V. Fadeeva; G. A. Eroshenko; G. N. Odinokov; N. A. Sharapova; T. V. Valova; V. V. Kutyrev (Проблемы особо опасных инфекций, 2012)
Developed is the PCR assay for the detection of the structural genes of toxin co-regulated adhesion piluses - tcpA of different types. Determined are the universal primers, the usage of which provides for the detection of the stated above genes in V. cholerae of various serogroups. With the help of this PCR assay identified is a new variant of tcpA gene in toxigenic cholera vibrio of non-O1/non-O139 serogroup.